2015
DOI: 10.3390/w7126672
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Suspended Sand Availability under Different Flow Conditions of the Lowermost Mississippi River at Tarbert Landing during 1973–2013

Abstract: Rapid land loss in the Mississippi River Delta Plain has led to intensive efforts by state and federal agencies for finding solutions in coastal land restoration in the past decade. One of the proposed solutions includes diversion of the Mississippi River water into drowning wetland areas. Although a few recent studies have investigated flow-sediment relationships in the Lowermost Mississippi River (LmMR, defined as the 500 km reach from the Old River Control Structure to the river's Gulf outlet), it is unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Days at the low flow stage accounted for about 50% of the time, but they only transported ~20% of the total BML. Joshi and Xu (2015) studied suspended sand availability under different flow regimes using 41‐year suspended sand (SS) data measured at Tarbert Landing (Figure 1). They also found that intermediate flow transported the most SS (i.e., 21% flow for 34% SS load) and peak flow was the most effective range to deliver SS (i.e., 3% flow for 13% SS load).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Days at the low flow stage accounted for about 50% of the time, but they only transported ~20% of the total BML. Joshi and Xu (2015) studied suspended sand availability under different flow regimes using 41‐year suspended sand (SS) data measured at Tarbert Landing (Figure 1). They also found that intermediate flow transported the most SS (i.e., 21% flow for 34% SS load) and peak flow was the most effective range to deliver SS (i.e., 3% flow for 13% SS load).…”
Section: Discussionmentioning
confidence: 99%
“…Located about 10 km downstream of the ORCS, Tarbert Landing gauging station operated by the USACE has long‐term suspended sediment concentration data. Utilizing these data, Rosen and Xu (2014) quantified total suspended sediment and Joshi and Xu (2015) estimated suspended sand load for the past four decades at Tarbert Landing. Knox and Latrubesse (2016) estimated bedload transport using a time‐lapsed bathymetric method immediately downstream of Tarbert Landing.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a bulk density of 1.2 metric tons per cubic meter (i.e., a typical bulk density for silt-pure soil), the total volume of trapped sediment during the 2011 flood would be about 1.0 million metric tons. Joshi and Xu [43] analyzed the long-term relationship between discharge and sand load for Tarbert Landing and developed a daily discharge (q) and daily sand load (S) rating curve as below: From their study on a three-year sediment budget (2008-2010), Allison et al [16] reported an average loss of 67 MT/year total suspended sediment in the river reach from TBL to St. Francisville at river kilometer 419, and 80% of the sediment loss was sand, i.e., about 54 MT/year sand. They attributed the large loss to a deposition in the channel bed and overbank storage.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of climate changes and human activities leads to the underlying surface change of the big river, altering basin runoff process [1]. It is surely that the evolution of the relationship between Yangtze River and Poyang Lake accelerated after the Three Gorges Reservoir (TGR) and other controlling reservoirs in the main stream and tributaries, which have been put into operation.…”
Section: Introductionmentioning
confidence: 99%